Design of Student Values Information System At Stmik Methodist College Binjai - Aprida Br Tarigan; Reza Alamsyah; Ferdy Riza (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Information technology in this modern era has developed so fast and sophisticated. Every education sector is expected to be able to utilize information technology as a support for operational activities in producing information. STMIK Methodist Binjai is one of the institutions that uses computerization in its data processing, such as processing academic grades and making final grades in the form of Study Result Cards (KHS). The problems that occur today are related to the procedures carried out in the process of processing academic grades. Such as when filling out the KRS which still uses handwriting, and the printing of the KHS which is not updated because it is not well organized between lecturers and the study program.